Kekosongan Perlindungan Hukum Dalam Praktik Kebidanan Pada Kegawatdaruratan Maternal - Muryanti, Titik; Muhammad Junaidi; Endah Pujiastuti (JURNAL USM LAW REVIEW, 2026)
This study aims to analyse positive legal arrangements in Indonesia regarding the legal protection of midwives in maternal emergencies and to formulate a concept of protection that provides legal certainty. The high maternal mortality rate (AKI) in Indonesia often forces midwives to act quickly outside of formal authority. However, they remain vulnerable to criminalisation due to the absence of specific implementing rules after the enactment of Law No. 17 of 2023. The research method used is a normative-legal approach with a descriptive-analytical orientation, based on the literature, laws, and regulations. The results of the study show a gap between ’das sollen’ and ’das sein’, where midwives are still haunted by legal risks even when acting in good faith. As a solution, this study offers a novelty in the form of an integrative protection model that adopts best practices from New Zealand, including the application of the good faith clause, the Strengthening of the Protection of the Midwife Profession, the obligation to certify BEmONC, and the application of restorative justice in the resolution of medical disputes. The implementation of this model is expected to create a fair health legal system for health workers while guaranteeing the right to life of mothers and babies. Penelitian ini bertujuan untuk menganalisis pengaturan hukum positif di Indonesia terkait perlindungan hukum bidan dalam kegawatdaruratan maternal serta merumuskan konsep perlindungan yang memberikan kepastian hukum. Tingginya Angka Kematian Ibu (AKI) di Indonesia sering kali memaksa bidan bertindak cepat di luar kewenangan formal, namun mereka tetap rentan terhadap kriminalisasi karena belum adanya aturan pelaksana spesifik pasca berlakunya UU No. 17 Tahun 2023. Metode penelitian yang digunakan adalah yuridis normatif dengan pendekatan deskriptif analitis melalui studi literatur dan peraturan perundang-undangan. Hasil penelitian menunjukkan adanya kesenjangan antara das sollen dan das sein, di mana bidan masih dihantui risiko hukum meskipun bertindak dengan itikad baik. Sebagai solusi, penelitian ini menawarkan kebaruan berupa model perlindungan integratif yang mengadopsi praktik terbaik dari New Zealand, mencakup penerapan good faith clause, penguatan perlindungan profesi bidan, kewajiban sertifikasi BEmONC, serta penerapan restorative justice dalam penyelesaian sengketa medis. Implementasi model ini diharapkan dapat menciptakan sistem hukum kesehatan yang adil bagi tenaga kesehatan sekaligus menjamin hak hidup ibu dan bayi.